AB0900 Descriptive study of psoriatic arthritis in a historical cohort of 383 patients at a university hospital. (12th June 2018) - Prior Español, A.; Mateo, L.; Mihaylov, M.; Roca, J.; García Mira, Y.; Camins, J.; Casafont, I.; Gifre, L.; Riveros, A.; Holgado, S.; Martínez-Morillo, M.; Aparicio, M.; et al.
Abstract : Background: There are few recent large cohort epidemiological studies that analyse the clinical profile of patients with psoriatic arthritis (PsA) who require biological treatment, as well as pharmacological survival and reasons for the suspension of these treatments. Objectives: To describe the clinical, demographic, epidemiological and radiographic characteristics of patients with PsA in our centre, as well as pharmacological survival and reasons for the suspension of different biological treatments. Methods: Retrospective analysis of patients with PsA treated between 1985 and 2015 at a University Hospital with a referral area of 8 50 000 inhabitants. Demographic, clinical, laboratory and imaging data, as well as patients' clinical and medical treatment records. Results: The main characteristics of the cohort are summarised in table 1: Approximately one third of patients with PsA (32.3%) required treatment with a biological drug during the course of their disease. The most frequently prescribed first-line drugs (89.5%) were tumour necrosis factor-α inhibitors (TNFi). During the course of their disease, 27 (21.9%) patients who started biological treatment received a biological drug other than TNFi. Of the 124 patients who started treatment with a biological DMARD, more than half (65, 52.8%) required a change to a second drug, and of these, 27 (41.5%) changed to a third, with up to 7 different biological drugs required in one case. The mean survival time for the first bDMARD was 42.8±42.3 months, with secondary failure the most frequent cause of treatment change (37.8%), followed by adverse effects (27.1%) and primary failure (18.9%). The adverse effects registered were: 20% infections, 20% appearance of neoplasms, 5% allergic reactions and 55% other causes. Conclusions: PsA presents a similar distribution by sex and is usually diagnosed at around the age of 50, having been preceded by cutaneous involvement. PsA is an entity of considerable severity and up to a third of patients will require biological treatments during its evolution. More than half of them will receive a second biological treatment. The retention rate of each drug varies but tends to decrease with each drug change. Disclosure of Interest: None declared